Effect of catechol-O-methyltransferase (rs4680) single-nucleotide polymorphism on opioid-induced hyperalgesia in adults with chronic pain. (May 2019) - Hooten, W Michael; Hu, Danqing; Cunningham, Julie M; Black, John L
The catechol-O-methyltransferase Val158Met polymorphism has been associated with alterations in pain perception, but the influence of the polymorphism on pain perception in patients with chronic pain receiving daily opioid therapy has not been previously reported. The primary aim of this study was to investigate the effects of the catechol-O-methyltransferase Val158Met polymorphism on heat pain perception in a cohort of adults receiving daily opioid therapy for chronic pain. Adults with chronic pain consecutively admitted to an outpatient pain rehabilitation program who met inclusion criteria and were receiving daily opioid therapy were recruited for study participation (N = 142). Individuals were genotyped for catechol-O-methyltransferase Val158Met (rs4680), and the polymorphism was analyzed using an additive and codominant genotype models. The distribution of the Val158Met genotypes was 25% for Val/Val, 41% for Val/Met and 34% for Met/Met (Hardy–Weinberg, P  > 0.05). A main effect of genotype was observed for heat pain perception ( P  = 0.028). Under the codominant model of allele effects, exploratory post hoc pairwise comparisons adjusted for morphine equivalent dose and pain catastrophizing demonstrated that individuals with the Val/Met genotype were hyperalgesic compared to individuals with the Val/Val ( P  = 0.039) and Met/Met ( P  = 0.023) genotypes. No significant association was observed between heat pain perception and genotype under the additive model of allele effects. Among patients with chronic pain who were receiving daily opioids, the Val/Met genotype was associated with hyperalgesia using a measure of heat pain perception that has been previously indicative of opioid-induced hyperalgesia in other heterogeneous samples of adults with chronic pain. This study contributes to the emerging understanding of how catechol-O-methyltransferase activity affects pain perception in the context of daily opioid use, and these findings may be useful in the design of future trials aimed at investigating the potential efficacy of ß-2 adrenergic receptor antagonism for opioid-induced hyperalgesia.